Pengaruh Pemberian Gambir dari Uncaria gambir (Hunter) Roxb terhadap pH dan Tukak Lambung pada Tikus Putih Jantan - Suhatri Suhatri; Zet Rizal; Debhi Mutiara Iryanda (STIFARM Padang, 2015)
The effect of gambir Uncaria gambir (Hunter) Roxb on pH and gastric ulcers in male rats induced by 1 mL/200 gram body weight by oral admistration. The parameter taken to asses antiulcer activity were change of gastric acid pH and ulcer index to normal condition. The result indicate that the gambir Uncaria gambir (Hunter) Roxb at doses of 20 mg, 40 mg and 80 mg/Kg BB body weight significantly decreases the ulcer index with curative ratio were 51.93 %, 55.98 % and 63.90 % (Gambir of two days) and 68.43 %, 77.69 % and 82.61 % (Gambir of four days) with respect to control group. The gambir at 20 mg, 40 mg and 80 mg/Kg BB body weight also significanthy decrease the gastric acid pH to its normal value (P<0.05).